Enhancing Product Innovation Through Digital Value Resonance: Technology Readiness - Luthfy Purnanta; Agustinus Budi Santoso; Roymon Panjaitan; Edwin Zusrony (Relevance: Journal of Management and Business, 2022)
This study intends to investigate technology readiness and the proficient to strive digitally for various offerings across digital value resonance, primarily for small medium enterprises. Questionnaires and interviews were used to gather data from 204 small and medium-sized businesses. SEM-PLS approaches are used to evaluate the impact of information with a trajectory moderated by digital value resonance on product innovation. The findings demonstrated that the digital value resonance managed to avoid the link between technological preparedness and product innovation enhancement. The advantages of this study are in the synthesizing of proposed digital value resonance variables from the results of resource-based view theory propositions, which aids in connecting previous researcher gaps and adds to a new concept that can configure digital value at the level of competition and increase MSME innovation products.